Gotong royong sebagai cerminan identitas nasional dalam masyarakat pedesaan - ZAHRA, SALLYKA (Maliki Interdisciplinary Journal, 2026)
Gotong royong is a unique Indonesian culture that reflects the values ​​of mutual help, togetherness, kinship, solidarity and unity in community life. This mutual cooperation has become the national identity of Indonesia which has been passed down from generation to generation, especially among rural communities. This writing aims to discuss mutual cooperation as a national identity, factors in the formation of national identity, the role of mutual cooperation as a national identity, especially in rural communities. The method used is a library study method by reviewing various journals and other related scientific sources. The results of the discussion show that mutual cooperation has an important role in the social life of this country. Gotong royong is a culture passed down from generation to generation in Indonesia, especially in rural communities. However, due to developments over time and the influence of globalization, attitudes of materialism and individualism have emerged in society. Therefore, it is important to preserve mutual cooperation as a national identity.